PROSPECTS FOR DIGITAL UZBEKISTAN 2030: DEVELOPMENT OF A DIGITAL GOVERNMENT SYSTEM - Muydinov Eldorbek Aminjon ugli (Web of Journals Publishing, 2024)
This article examines the prospects for the development of the digital government system in Uzbekistan by 2030. The authors analyze the main directions of development of digitalization of public administration, highlight key problems and challenges, and also propose ways and mechanisms for solving them.
Keywords: Digital government, digitalization , information technology, e-government, cybersecurity , digital literacy, efficiency, public administration, development.